(untitled) (New York, 1994)
This book is a guide to understanding the cell biology concerned with eucaryotic cells. In Part I and Part II of this book, the eucaryotic cells that form multicellular animals and plants are social organisms to an extreme degree: they live by cooperation and specialization. To understand how they function, one must study the ways of cells in multicellular communities, as well as the internal workings of cells in isolation. Part III of the book is devoted to the behavior of cells in multicellular animals and plants. Thus developmental biology, histology, immunobiology, and neurobiology are discussed
Keywords: Cells,Cytology,Molecular biology